Analisis pengaruh ekspor, impor, nilai tukar rupiah dan inflasi terhadap pertumbuhan ekonomi Indonesia tahun 2000- 2019 - Slamet, Agung; Hidayah , Anisa Nur (Nur Science Institute, 2021)
Economic growth is a measure of progress or failure of the economy in a country, especially in Indonesia, because the level of factors of production of goods and services will affect the ongoing economic development. This study aims to determine and analyze the effect of exports, imports, the rupiah exchange rate, and inflation on economic growth in Indonesia for the 2000-2019 period. The dependent variable of this research is economic growth. In contrast, the independent variable is export, import, rupiah exchange rate, and inflation in seeing the effect of the independent variable on the dependent variable in this study using multiple linear regression analysis. The results showed that the export variables and the rupiah exchange rate had a positive effect, while the import and inflation variables did not affect economic growth.